2004
DOI: 10.1007/s00335-004-3007-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic analysis of seizure susceptibility in PL/J mice

Abstract: Epilepsy is one of the most common but genetically complex neurological disorders in humans. Identifying animal models that recapitulate human epilepsies is important for pharmacological studies of anticonvulsants, dissection of molecular and biochemical pathogenesis of epilepsy, and discovery of epilepsy susceptibility genes. We discovered that the PL/J inbred mouse strain is susceptible to handling- and rhythmic tossing-induced seizure. The tonic-clonic and generalized seizures observed after induction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In the present study, C58/ J, PL/J, and SWR/J all demonstrated poor learning during the initial phase of the T-maze task. The low performance in the PL/J strain may have been due, in part, to the seizure-like responses characteristic of this strain [21]. So far, only one strain, SJL/J, has shown rapid acquisition of the task, without meeting criterion for learning during reversal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, C58/ J, PL/J, and SWR/J all demonstrated poor learning during the initial phase of the T-maze task. The low performance in the PL/J strain may have been due, in part, to the seizure-like responses characteristic of this strain [21]. So far, only one strain, SJL/J, has shown rapid acquisition of the task, without meeting criterion for learning during reversal.…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the study, a distinctive, persistent back-flipping behavior was observed in all 5 home cages of C58/J mice (with 4 mice per cage). Observations of another strain, PL/J, indicated that 30% of the mice had seizurelike responses during the social approach tests (see [21]). …”
Section: 1a Observational Measures-initialmentioning
confidence: 99%
“…Such cable-based systems hardly impose problems for studies of seizures that rely on electrical or chemical induction. However, in many epilepsy models, the most studied being the El mouse, seizures appear during complex stimulus situations such as daily handling procedures (Etholm and Heggelund, 2009;Kitami et al, 2004;Todorova et al, 1999). In such studies cable-based systems cause problems because one would try to mimic situations where seizures are normally seen.…”
Section: Introductionmentioning
confidence: 99%
“…Problems with evoking seizures during EEG-recording can be bypassed by using pharmacological agents (Nakano et al, 1994), but this may seriously change the nature of the seizure studied. The risk of changing the phenomenon studied is also present in cases where the stimulus intensity is increased by for instance replacing simple cage changing procedures with more traditional tossing procedures (Imaizumi et al, 1959), or where one is changing such tossing regimes to make them practical with cable-tethered animals (Etholm and Heggelund, 2009;Kitami et al, 2004;Suzuki and Nakamoto, 1977). Moreover, such elaborate movement regimes (Imaizumi et al, 1959) can induce large movement artifacts, especially during the initial parts of the seizures that are often of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Many mouse strains (including C3H) carry a mutation in the Pde6b gene that causes severe retinal generation (Pittler and Baehr, 1991); others (such as I/Ln) carry mutations such as piebald with defects in the development of the neural crest; these are just two of many examples (Bogue, 2003). In the field of epilepsy, several mouse strains (e.g., EL, SWXL-4, PL) exhibit tonic-clonic and generalized convulsions with routine handling (Rise et al, 1991;Frankel et al, 1994;Kitami et al, 2004). In some strains, it has been shown that convulsions are explained by the inheritance of susceptibility alleles from nonepileptic parental strains (Frankel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%